2019
DOI: 10.1186/s40663-019-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations in productivity and water use efficiency across a temperate forest landscape of Northeast China

Abstract: Background: Forests are increasingly valued for non-timber ecosystem services in place of conventional wood fiber production. Biomass carbon sequestration is one of the key ecosystem services forests are relied upon for mitigating global climate change. However, planning for large-scale tree planting and managing established forest stands for carbon sequestration require careful consideration of the gain in biomass production and tradeoff for other regulatory services. How a tradeoff between forest production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 66 publications
1
17
1
Order By: Relevance
“…The first-rotation density declines as the age increases over a long term, up to 50 (Xie et al 2016) or 90 years (Selvaraj et al 2017). Stand density is an influential factor that determines biomass C sequestration and consequently physiological activities in trees (Devi and Yadava 2015;Xie et al 2016;Li et al 2019;Pan et al 2019). Older stands resulted in greater tree C storage and higher partition of biomass to the root (Xie et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The first-rotation density declines as the age increases over a long term, up to 50 (Xie et al 2016) or 90 years (Selvaraj et al 2017). Stand density is an influential factor that determines biomass C sequestration and consequently physiological activities in trees (Devi and Yadava 2015;Xie et al 2016;Li et al 2019;Pan et al 2019). Older stands resulted in greater tree C storage and higher partition of biomass to the root (Xie et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Continentally and globally, climate appears to the most important factor shaping the spatial patterns of forest carbon stocks (Pan et al 2011;Zhou et al 2019), and locally and regionally, the density and partitioning of forest carbon varies with tree species, forest structure and types, stand development, management, and soil conditions (Giardina and Ryan 2000;Law et al 2004;Sun et al 2004;Li et al 2019). Marked differences can been found in forest carbon in relation to forest types, development, and site conditions regionally (Law et al 2004) and at landscape-scale (Li et al 2019), and between natural and planted forests (Yu et al 2019). Natural and anthropogenic disturbances, accidental or intentional, are all detrimental to the stock and stability of forest carbon pools.…”
Section: Forest Carbon Sequestrationmentioning
confidence: 99%
“…Realizations of the vital roles of forests in environmental regulations and eco-safety have promoted the development and management of plantation forests for non-timber products and/or services in modern forestry (Haakana et al 2020;Temperli et al 2020). Increased carbon sequestration capability and effective water conservation benefits are two of the key services highly regarded for forest ecosystems (Li et al 2019). Over the decades, numerous studies have been conducted to quantify the capacity and controls of forest carbon sequestration, and to determine the regulatory roles of forests in local and regional water cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Inbreeding depression mainly results from either selfing or correlated mating (Jain 1976;Ritland 1989;Keller and Waller 2002). Plant pollination dynamic research has indicated that the majority of mating occurred within a certain distance between individuals, thus it is necessary to highlight the importance of separating related individuals beyond the effective pollen dispersal distance (Levin and Kerster 1974;Adams and Birkes 1991;Li et al 2019;Zhang et al 2019). The concern over inbreeding build-up in seed orchard crops necessitated the development of orchard designs aimed at separating relatives (Giertych 1975).…”
Section: Introductionmentioning
confidence: 99%